Probability of a ship becoming beset in ice along the Northern Sea Route – A Bayesian analysis of real-life data - Vanhatalo, Jarno; Huuhtanen, Juri; Bergström, Martin; Helle, Inari; Mäkinen, Jussi; Kujala, Pentti (Cold Regions Science and Technology)
2021